System wychowawczy Antoniego Makarenki jako podstawa do reorganizacji opieki nad dzieckiem osieroconym w świetle peerelowskiego czasopiśmiennictwa pedagogicznego - Andrzej Kołakowski (Problemy Wczesnej Edukacji)
The aim of this article is to show the influence of Makarenko’s conception of upbringing on the reorganising of the orphan care system in the PRL. A valuable source of information on the subject are pedagogical periodicals, which enable us to reconstruct the degree to which Makarenko’s views were implemented and determine which of his ways and methods of upbringing caught on in Polish orphanages. The author also raises the question of how the collective upbringing system could be an inspiration for educators today.